Các giải pháp cho phần mềm chống virus thông minh - Thủy, Nguyễn Quang; Quang, Trương Minh Nhật (Journal of Computer Science and Cybernetics, 2016)
In this paper we shall propose some solutions for an intelligent anti-virus system which are investigated also in the system D2. Principles of such solutions will be detailed. The implementation is being carried out, showing promising results.